2015
DOI: 10.1108/bfj-08-2013-0235
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of food quality in Malaysia

Abstract: Purpose -This paper was written to gain an understanding of the quality cues that consumers look for in purchasing fresh meat and fresh fruit and vegetables in Malaysia. Through a perceived quality model, this paper identifies the implicit, intrinsic, extrinsic and credence quality cues consumers' use in their decision to purchase fresh meat and fresh fruit and vegetables.Design/methodology/approach -This study utilised the shopping mall intercept survey method. Data were collected from traditional markets and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 51 publications
(70 reference statements)
10
60
0
1
Order By: Relevance
“…This finding was in agreement with previous studies that highlighted one or more of these cues as the most important in food quality evaluation [1,112]. Similarly, a study on Malaysian consumers highlighted that freshness and price were two of the most used quality cues for fresh meat, fruits, and vegetables, and freshness was judged by the physical appearance of the meat [50]. The price can be regarded as a motive to purchase, as an indicator of quality, and as an indicator of socio-economic status [113].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding was in agreement with previous studies that highlighted one or more of these cues as the most important in food quality evaluation [1,112]. Similarly, a study on Malaysian consumers highlighted that freshness and price were two of the most used quality cues for fresh meat, fruits, and vegetables, and freshness was judged by the physical appearance of the meat [50]. The price can be regarded as a motive to purchase, as an indicator of quality, and as an indicator of socio-economic status [113].…”
Section: Resultssupporting
confidence: 91%
“…In the total food quality model, Grunert et al [48] employed the term "cues", and he identified two moments for their use, that is for quality evaluation (before purchase, when consumers form quality expectations, and after purchase, when consumers undergo the quality experience). Other studies, which investigated food quality evaluation by consumers, also used the term "cues" [49][50][51]. The current study investigated food quality evaluation at the purchasing moment; therefore, we adopted Steenkamp's [48] definition, and the term quality "cues" was used.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…However, a lack of market demand for locally-produced products has weakened this innovation. Consumers are often concerned about the quality and safety of locally-produced food [1]. The lack of consumer interest in purchasing local products is mainly due to their low quality, a low level of differentiation, market segmentation, and the development of specific client niches [2].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the dried food products can be very well identified by sensory perceptions, and consumers mostly notice the colour and texture as indicators . Pre‐drying treatment is often carried out in different food products to reduce enzymatic spoilage and further adverse changes during different drying processes.…”
Section: Introductionmentioning
confidence: 99%